The Latest Digital Information Technologies and Computer Programs in Integration and in Improvement with the Method of Training and Education of Froebel and His "Gifts" - Gulshod Yunusova Nazikhovna (Zien Journals, 2022)
This article shows the integration of the latest information technologies and computer programs with the methodology of F. Fröbel in the early period of children's education in children's educational institutions. The famous method of teaching F. Fröbel, his exercises and "gifts" are known, with the help of which the child begins to learn about objects and the world around him in general, learns the forms of the object, gets acquainted with spatial figures, which further help him master mathematics, geometry, take the initial step into spatial stereometry. He beginsto get acquainted with objects, understanding their properties of smoothness, roughness, and then roundness, sharp edges, that some figures roll, and others fall to their faces, there are figures with which you can do both. "Gifts" by F. Fröbel gradually prepare the child and introduce him to an interesting world. The most interesting is the use of the latest information technologies, platforms, sites for the development of the child along with these gifts. Computer programs and sites created by the author will come to the rescue here. Ready-made online resources of other scientists and teachers. As a result of the research, the author determined the effectiveness of integrated teaching of children by the method of F. Fröbel in the environment of information technologies and computer programs, proving the effectiveness of integrated learning with updated modern methods.
Keywords: information digitaltechnologies; computer programs; improvement of methodology; Fröbel's